Answer:
2q +6
Explanation:
The distributive property is used for this purpose. The factor outside parentheses (2) multiplies each of the terms inside parentheses (q, 3).
2(q +3) = 2·q +2·3 = 2q +6
_____
Additional comment
It might help to think of the parentheses as a "bag" containing one "q" and 3 tokens. The number outside parentheses tells you how many "bags" you have. Expanding the expression is equivalent to dumping out the bags and describing the total contents:
2(q +3) = (q +3) +(q +3) . . . . multiplication is the same as repeated addition
= (q +q) +(3 +3)
= 2q +6